The drowning kind - McMahon, Jennifer, 1968- (Scout Press, 2021)
"From the New York Times bestselling author of The Winter Sister comes a new work of psychological horror about a therapist who returns to the old family home after her sister drowns in its swimming pool, where she discovers that it has something sinister lurking beneath its surface"--